Effect of EPDM as a compatibilizer on mechanical properties and morphology of PP/LDPE blends. (July 2013) - Penava, Nina Vranjes; Rek, Vesna; Houra, Ivona Fiamengo
Blends of polypropylene (PP) and low-density polyethylene (LDPE) with and without ethylene-propylene-diene (EPDM) terpolymer as a compatibilizer were studied. Mechanical properties were chosen to estimate the compatibilization efficiency of EPDM. The interactions between phases were valued through glass transition shifts in dynamic mechanical spectra, and morphology of the blends was obtained using scanning electron microscopy. Interfacial adhesion was improved by EPDM addition. Addition of EPDM to PP/LDPE blends improved mechanical properties, especially Izod impact strength in LDPE-rich blends and with higher EPDM content.